Academic mobility and the labor market - Jumabayeva, Zhanna (NUGSE Research in Education, 1(1), 2016)
The current study is aimed to better understand the concept of academic mobility and identify its labor market outcomes in the context of Kazakhstan. The paper considers whether mobility is an advantage for the domestic employment market and whether it enhances graduates’ employability. The researcher also investigates whether in Kazakhstan students’ participation in the international programs, particularly the Bolashak International Scholarship of the President of the Republic of Kazakhstan, affects their employment upon completion of their studies. This investigation indicates that increasingly large numbers of students continue to study abroad despite the lack of clear evidence supporting the gains graduates have in finding jobs. This suggests that students who return are not necessarily guaranteed with ideal jobs upon their graduation. Just because someone studied abroad, the competition for them does not disappear: work experience can have a higher priority. Hence, the results of this study showed that the Bolashak program is not always a ticket to a better future, at least in the short term.
Keywords: academic mobility; labor market; Bolashak program; employability